Analisis Pengaruh Earning.per.Share (EPS), Price to.Book Value (PBV), Return on Asset (ROA), Current.Ratio (CR), dan Debt to Equity Ratio (DER) Terhadap Return Saham Pada Perusahan Manufaktur Subsektor Food and Beverage yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2013-2020 - Dandi Prastyawan; Gendro Wiyono; Pristin Prima Sari (Universitas Batanghari Jambi, 2022)
Return (return) is one of the goals of investors investing in the world of capital markets. There are various ways that investors do, in order to get the expected return. So investors need to analyze and also consider things that can affect stock returns. The purpose of this study was to determine the effect of Earning per Share (EPS), Price to Book Value (PBV), Return on Assets (ROE), Current Ratio and Debt to Equity Ratio (DER) on Stock Returns in Manufacturing Companies in the Food and Beverage Subsector that listed on the IDX for the period 2013-2020. The population used in this study are food and beverage companies listed on the IDX for the period 2013-2020. This study used purposive sampling technique to obtain the number of samples. Based on this technique, 14 companies were obtained to be used as samples. The data analysis technique used in this research is multiple linear regression and hypothesis testing (F test and t test) with an alpha significance level of 5%. The results of this study indicate that the variables EPS, PBV, and CR have a negative and significant effect on stock returns. The ROA variable has a positive and significant effect. While the DER variable has no effect and simultaneously shows that there is an influence between EPS, PBV, ROA, CR, and PBV on stock returns. This research is only limited to food and beverage sector companies listed on the IDX, so that further researchers are advised to extend the research period and expand the research population. And consider other variables that can affect stock returns.